Oreste Besson Rank and Certainty Factor for Digital Business Investment Decisions - Rofi'i, Yulianto Umar (International Journal Software Engineering and Computer Science (IJSECS), 2023)
This study analyzes investment decision making in digital business using the Oreste Besson Rank and Certainty Factor methods. A mixed qualitative and quantitative approach is used to understand the qualitative factors that influence investment decisions and measure the effectiveness of analytical methods. The results of the qualitative analysis of the in-depth interviews highlight key factors: brand reputation (42% response), technology adaptability (35% response), and long-term growth potential (23% response). Uncertainty of technology and market changes (75% of respondents) affects investment strategy. Quantitative analysis uses the Decision Support System (SPK) and Besson-Rank methods to generate investment alternatives. Digital Properties rank the best, with Besson-Rank weighting the criteria score for a more in-depth look. The Certainty Factor (CF) method assesses investment options based on available data, with E-commerce Growth having the highest score, indicating a higher priority. The internal noise test confirms the Oreste Besson Rank and Certainty Factor methods as reliable tools, providing investment ratings and risk assessments consistent with simulated data. The results of this study underscore the importance of reputation, technology adaptability, and growth potential in digital business investment decisions. The Oreste Besson Rank and Certainty Factor methods are effective in providing accurate guidance. This research provides deeper insight into investment decision-making in a dynamic digital business and proposes recommendations for optimizing this analytical method in the face of market changes.